The Hygiene Hypothesis – Learning From but Not Living in the Past - Pfefferle, Petra I.; Keber, Corinna U.; Cohen, Robert M.; Garn, Holger (Frontiers in Immunology, 2021)
Postulated by Strachan more than 30 years ago, the Hygiene Hypothesis has undergone many revisions and adaptations. This review journeys back to the beginnings of the Hygiene Hypothesis and describes the most important landmarks in its development considering the many aspects that have refined and generalized the Hygiene Hypothesis over time. From an epidemiological perspective, the Hygiene Hypothesis advanced to a comprehensive concept expanding beyond the initial focus on allergies. The Hygiene Hypothesis comprise immunological, microbiological and evolutionary aspects. Thus, the original postulate developed into a holistic model that explains the impact of post-modern life-style on humans, who initially evolved in close proximity to a more natural environment. Focusing on diet and the microbiome as the most prominent exogenous influences we describe these discrepancies and the resulting health outcomes and point to potential solutions to reestablish the immunological homeostasis that frequently have been lost in people living in developed societies.